The characteristics and classification of eastward‐propagating mesoscale convective systems generated over the second‐step terrain in the Yangtze River Valley. (26th December 2018) - Yang, Ruyi; Zhang, Yuanchun; Sun, Jianhua; Fu, Shenming; Li, Jun
Abstract : A total of 316 eastward‐propagating mesoscale convective systems (MCSs) that form over the second‐step terrain are detected during May to August 2000–2016 (except 2005) using an hourly black body temperature (TBB) dataset. These MCSs last from three to dozens of hours and moved along various trajectories. These detected MCSs are divided into four categories (i.e., C1, C2, C3, and C4) according to their key characteristics. C1 MCSs generally move in a northeastward direction to northern China and have a mean duration of 16 hr, while their C2 counterparts are mostly characterized by quasi‐stationary behavior over the eastern edge of the second‐step terrain and have a 9‐hr mean life span approximately. In contrast, most C3 MCSs move in an eastward direction and tend to last 21 hr on average, inducing heavy rainfall from the eastern edge of the second‐step terrain to the coastline. The C4 MCSs possess similar features to C3 MCSs but have much shorter mean durations ( 8 hr) and exert influences within an area mainly limited to the middle reaches of the Yangtze River Valley. Composite analyses of these four MCS categories show that a strong lower‐level cyclonic vorticity in all categories favors the MCSs' sustainment; the differences of the steering flow from middle‐to‐upper levels account for the different moving directions of the four categories; the intensity of imported water vapor is proportional to the longevity of MCSs. Abstract : The mesoscale convective systems (MCSs) generated over the second‐step terrain could move eastward and influence precipitation in downstream regions. A total of 316 eastward‐propagating MCSs that generated over the second‐step terrain during May to August 2000–2016 (except 2005) using hourly black body temperature dataset and classified these eastward‐propagating systems into four categories according to their key characteristics. These MCSs contributed significantly to the seasonal heavy rainfall over the middle and lower reaches of the Yangtze River.